Prevalence of Hypokalemia and Primary Aldosteronism in 5100 Patients Referred to a Tertiary Hypertension Unit. Issue 4 (April 2020) - Burrello, Jacopo; Monticone, Silvia; Losano, Isabel; Cavaglià, Giovanni; Buffolo, Fabrizio; Tetti, Martina; Covella, Michele; Rabbia, Franco; Veglio, Franco; Pasini, Barbara; Williams, Tracy Ann; Mulatero, Paolo
Abstract : Primary aldosteronism (PA) was considered a rare disorder almost always associated with hypokalemia. The widespread screening of patients with hypertension unveiled an increased prevalence of PA with normokalemic hypertension the prevailing phenotype. Many studies have reported the prevalence of hypokalemia in patients with PA; conversely, the prevalence of PA in patients with hypokalemia is unknown. In this retrospective observational study, we define the prevalence of hypokalemia in referred patients with hypertension and the prevalence of PA in patients with hypokalemia and hypertension. Hypokalemia was present in 15.8% of 5100 patients with hypertension, whereas 76.9% were normokalemic, and 7.3% hyperkalemic. The prevalence of PA in patients with hypokalemia was 28.1% and increased with decreasing potassium concentrations up to 88.5% of patients with spontaneous hypokalemia and potassium concentrations <2.5 mmol/L. A multivariate regression analysis demonstrated the association of hypokalemia with the occurrence of cardiovascular events independent of PA diagnosis. An association of PA with the occurrence of cardiovascular events and target organ damage independent of hypokalemia was also demonstrated. In conclusion, our results confirm that PA is a frequent cause of secondary hypertension in patients with hypokalemia, and the presence of hypertension and spontaneous hypokalemia are strong indications for PA diagnosis. Finally, we show that PA and hypokalemia are associated with an increased risk of cardiovascular events. Abstract : Supplemental Digital Content is available in the text.